2001
DOI: 10.2307/2657023
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers reveal little genetic differentiation among Aconitum noveboracense and A. columbianum (Ranunculaceae) populations

Abstract: Aconitum noveboracense, a rare, herbaceous perennial, is restricted to recently unglaciated areas in Iowa, Wisconsin, Ohio, and New York, and federally classified as a threatened species. These populations may be disjuncts of the common congener, A. columbianum Nutt., which occurs in the mountains of the western United States. Morphological characters do not reliably separate these taxa. The identity of Black Hills populations, located between the ranges of the rare and common species, is also uncertain. We ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…Molecular methods in combination with traditional sources of evidence have repeatedly been used to assess the systematic status of rare and endangered plant taxa (Baskauf et al, 1994;Van Buren et al, 1994;Cole and Kuchenreuther, 2001;Klips, 1995;Walters and DeckerWalters, 1993;Wyatt et al, 1992) resulting in recognition, rejection, or change of formal systematic status. The phylogenetic relationship between Oe.…”
Section: Taxonomic Statusmentioning
confidence: 99%
“…Molecular methods in combination with traditional sources of evidence have repeatedly been used to assess the systematic status of rare and endangered plant taxa (Baskauf et al, 1994;Van Buren et al, 1994;Cole and Kuchenreuther, 2001;Klips, 1995;Walters and DeckerWalters, 1993;Wyatt et al, 1992) resulting in recognition, rejection, or change of formal systematic status. The phylogenetic relationship between Oe.…”
Section: Taxonomic Statusmentioning
confidence: 99%
“…LeCorre et al (1997), Mamuris et al (1999), Sun et al (1999) and Cole and Kuchenreuther (2001) found that clusters obtained with these markers differed. The larger number of loci resolved by RAPDs compared to allozymes, the selective neutrality of RAPDs and their ability to screen a larger part of the genome were cited as possible factors for the incongruences observed.…”
Section: Studymentioning
confidence: 99%
“…barnebyana really is a distinct taxon deserving protection. Similar conservation questions were addressed, for example, in the midwestern North American taxa Aconitum noveboracense (Cole and Kuchenreuther, 2001) and Sedum integrifolium subsp. leedyi (Olfelt et al, 2001), and the Californian Eriastrum densifolium (Brunell and Whitkus, 1997) by using random amplified polymorphic DNA (RAPD) analysis.…”
mentioning
confidence: 97%